Enhanced direct interspecies electron transfer with transition metal oxide accelerants in anaerobic digestion. Issue 6 (January 2021) - Yun, Sining; Xing, Tian; Han, Feng; Shi, Jing; Wang, Ziqi; Fan, Qingyang; Xu, Hongfei
Graphical abstract: Highlights: Four transition metal oxides promote the anaerobic digestion by enhanced DIET. First-principle calculations illustrate the metallic feature of accelerants. Mediated electrochemical tests verify an electron exchange capacity of accelerants. Microbial community confirms the syntrophic bacteria in anaerobic digestion. A universal strategy for understanding the enhanced DIET is proposed. Abstract: Transition metal compounds have been widely used to enhance the anaerobic digestion (AD) performance, while the role of transition metal compounds in enhancing AD performance remains unclarified. In this work, the function of transition metal oxide accelerants (tantalum oxide, niobium oxide, hafnium oxide, and tungsten oxide) in enhanced AD systems was investigated from experimental and theoretical standpoints. Higher biogas production (565.01–617.85 mL/g VS), chemical oxygen demand degradation rate (67.17%-70.45%), total solids and volatile solids reduction rates (29.76%-34.71%, 51.83%-60.88%) were achieved in AD systems with transition metal oxide accelerants than the control (327.08 mL/g VS, 56.65%, 22.65%, and 41.18%). The first-principle density functional theory calculations, electron exchange capacity analysis, and the 16S rRNA gene pyrosequencing demonstrated superior electron transfer and exchange capacities as well as microbial consortia development in transition metal oxides-induced DIET mechanism. This work provides a promising strategy for understanding the function of high-performance accelerants in AD systems.